Neuroprotective Effects of Shenqi Fuzheng Injection in a Transgenic SOD1-G93A Mouse Model of Amyotrophic Lateral Sclerosis - Sugimoto, Kazuo; Liu, Jia; Li, MingXuan; Song, YueBo; Zhang, Chi; Zhai, ZhiGuang; Gao, Ying (Frontiers in Pharmacology, 2021)
Background: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, in the pathogenesis of which oxidative stress (OS) was believed to play a key role. Shenqi Fuzheng Injection (SFI) concocted from two kinds of Chinese medicinal herbs: Radix Codonopsis and Radix Astragali was proven to be eligible to reduce the OS injury and increase the activity of nuclear factor-E2-related factor (Nrf2) pathway, an antioxidant enzymes inducer. Objective: We aim to investigate the effects and potential mechanisms underlying the action of SFI on a well-established transgenic mouse model of ALS. Methods: Transgenic SOD1-G93A mice were intraperitoneally injected with SFI (40mL/kg) three times a week from 87 days of age. The motor function, survival, pathological manifestations in the brain, and Nrf2 pathway-related assessments of the mice were performed. Results: SFI treatment efficiently postponed the disease onset (P = 0.022) and extended the overall survival (P = 0.038) of the SOD1-G93A mice. Moreover, SFI significantly reduced the motor neurons loss (P < 0.001) and astrocytic activation (P < 0.05) in the motor cortex of the brain of SOD1-G93A mice at 130 days of age. The protective effects of SFI in the SOD1-G93A mice were associated with decreasing the level of malondialdehyde (P < 0.05), and increasing the levels of superoxide dismutase (P < 0.05), Nrf2 (P < 0.05), Heme Oxygenase-1 (P < 0.05) and Glutathione S-transferase (P < 0.05) in the SOD1-G93A mice. Conclusions: The SFI treatment efficiently extended the overall survival and improved the pathological manifestations of the brain via alleviating the OS injury and activating the Nrf2 pathway in the animal model of ALS, which made SFI a potentially promising candidate for ALS treatment.